2021
DOI: 10.5858/arpa.2020-0774-ra
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Findings in Surgical Pathology Specimens From Individuals Taking Masculinizing Hormone Therapy for the Purpose of Gender Transition

Abstract: Context.— Transgender men and transmasculine persons experience a discordance between the female sex they were assigned at birth and their gender. They may choose to take hormone therapy and/or undergo surgery to masculinize the body. Understanding the common (and less common) histologic changes present in patients taking masculinizing hormones will empower pathologists to better serve this unique patient population. Objective.— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…34,35 However, even early reports noted its association with androgen and testosterone therapies, and it is now recognized as a common finding in histology specimens from patients undergoing exogenous testosterone therapy, being observed in up to 88.2% of Pap tests from transgender patients. 22,29,36 In this current study, it was found in 43% of cases. Transitional cell metaplasia, as the name implies, is a metaplastic process where the epithelium morphologically resembles urothelium; it is considered by some to be a morphological variant of atrophy or basal cell hyperplasia.…”
Section: The Major Cytomorphologic Features Ofsupporting
confidence: 56%
See 1 more Smart Citation
“…34,35 However, even early reports noted its association with androgen and testosterone therapies, and it is now recognized as a common finding in histology specimens from patients undergoing exogenous testosterone therapy, being observed in up to 88.2% of Pap tests from transgender patients. 22,29,36 In this current study, it was found in 43% of cases. Transitional cell metaplasia, as the name implies, is a metaplastic process where the epithelium morphologically resembles urothelium; it is considered by some to be a morphological variant of atrophy or basal cell hyperplasia.…”
Section: The Major Cytomorphologic Features Ofsupporting
confidence: 56%
“…In the older literature, transitional cell metaplasia was predominantly described in peri‐ and postmenopausal women, the majority of whom were not on exogenous hormones 34,35 . However, even early reports noted its association with androgen and testosterone therapies, and it is now recognized as a common finding in histology specimens from patients undergoing exogenous testosterone therapy, being observed in up to 88.2% of Pap tests from transgender patients 22,29,36 . In this current study, it was found in 43% of cases.…”
Section: Discussionmentioning
confidence: 42%
“…Also, the scientific literature concerning individuals taking masculinizing hormone therapy is rather sparse and mainly restricted to histologic changes [60]. For example, prostatic metaplasia was described in the cervical epithelium [60]. Although the RT-PCR results (Figure 5) were obtained from a single individual only, they are of considerable clinical interest, as we show here, for the first time, that mucin and FCGBP expression in the endocervix can be subject to differential regulations due to hormonal treatment.…”
Section: Transcriptional Profiling Of the Human Endocervix And Vagina...mentioning
confidence: 79%
“…However, differential regulation of MUC5AC and MUC5B expression by estradiol has been reported recently [59]. Also, the scientific literature concerning individuals taking masculinizing hormone therapy is rather sparse and mainly restricted to histologic changes [60]. For example, prostatic metaplasia was described in the cervical epithelium [60].…”
Section: Transcriptional Profiling Of the Human Endocervix And Vagina...mentioning
confidence: 99%